(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study explores the integration of AI-powered platforms to enhance differentiated instruction in university-level English as a Foreign Language (EFL) classes. It examines how artificial intelligence tools can be used to personalize learning, address diverse student needs, and optimize teaching strategies. The research highlights the potential of AI to provide adaptive learning pathways, automated feedback, and data-driven insights into student performance. By leveraging AI technologies, educators can create more engaging, efficient, and student-centered learning environments, ultimately improving language acquisition outcomes.